Extensive linear porokeratosis in an 8-year-old female. - Theriot, T.; Haas, C.; Hill, I. (European Journal of Pediatric Dermatology, 2024)
An 8-year-old female presented with extensive lesions involving the left leg, arm, and face which had been present since birth with biopsy in infancy suggestive of a scar. Clinical examination revealed hyperpigmented, hyperkeratotic papules coalescing into linear plaques. Repeat biopsy confirmed the diagnosis of linear porokeratosis. This case is a valuable example of a rare condition which may present a diagnostic challenge. It underscores the importance of considering linear porokeratosis in the differential diagnosis of linear dermatoses and highlights the need for a comprehensive approach to diagnosis and management.